2009
DOI: 10.1111/j.1464-0597.2008.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Majority Attitudes toward Multiculturalism in the Netherlands between 1999 and 2007

Abstract: The success of multiculturalism as an ideology to deal with cultural differences depends upon the level of support for multiculturalism by majority members. It has been argued that support for multiculturalism in the Netherlands has substantially changed in response to various national and international events, such as the terrorist attacks on New York (n = 464). Contrary to popular belief, we found little evidence for enduring attitude changes over the nine-year period. Implications for studies of multicultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
1
17
0
4
Order By: Relevance
“…In terms of symbolic threat, research suggests that natives of a host society would be more willing to accept immigrants if they believe that immigrants will not change the host society's cultural values and way of life (Card, Dustmann, & Preston, ; Hainmueller & Hiscox, ). Indeed, the acculturation literature also demonstrates a clear preference among natives of a host society for immigrants to adapt to the host society's culture (Breugelmans, van de Vijver, & Schalk‐Soekar, ; Verkuyten & Martinovic, ). Immigrants who are culturally very different from the host society are more likely to be perceived as threatening, but when these immigrants are perceived to be adapting to the host society's culture, the level of threat declines (Rohmann, Florack, & Piontkowski, ).…”
Section: Perceived Threats and Immigrant Helpingmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of symbolic threat, research suggests that natives of a host society would be more willing to accept immigrants if they believe that immigrants will not change the host society's cultural values and way of life (Card, Dustmann, & Preston, ; Hainmueller & Hiscox, ). Indeed, the acculturation literature also demonstrates a clear preference among natives of a host society for immigrants to adapt to the host society's culture (Breugelmans, van de Vijver, & Schalk‐Soekar, ; Verkuyten & Martinovic, ). Immigrants who are culturally very different from the host society are more likely to be perceived as threatening, but when these immigrants are perceived to be adapting to the host society's culture, the level of threat declines (Rohmann, Florack, & Piontkowski, ).…”
Section: Perceived Threats and Immigrant Helpingmentioning
confidence: 99%
“…Moreover, immigrants that are seen as unthreatening to the host society's culture elicit more positive attitudes among members of the host society (Stephan, Renfro, Esses, Stephan, & Martin, ). Fortunately, immigrants often possess high endorsement of multicultural attitudes, which entails that they are willing to adapt to the host society's culture to a meaningful extent (Arends‐Tóth & van de Vijver, ; Breugelmans et al., ; Verkuyten & Martinovic, ). However, while immigrants may be exerting effort to adapt to the host society's culture, the host society may not necessarily see these efforts (Navas et al., ).…”
Section: Perceived Threats and Immigrant Helpingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant cultural group could feel realistic threat and anxiety towards unknown cultural habits and values of minority groups, and, as a result could require the minority groups to adapt to the existing standards (Stephan & Stephan, 1996). In this context, it could be interesting to explain the differences between the military organizations in both countries on the bases of societal differences level like stability of democracy and ratings of integration policy (Bourhis, Moï se, Perreault, & Sené cal, 1997) or societal values (Breughelmans, Van de Vijver & Schalk-Soekar, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This means that the ideological content of multiculturalism corresponds with the core attitude dimensions of traditionalism (vs. change) and equality (vs. dominance) underlying political orientation and education. Research has found a positive link between education and multiculturalism, and between left-wing political orientation and multiculturalism (e.g., Breugelmans & Van de Vijver, 2004;Breugelmans, Van de Vijver, & Schalk-Soekar, 2009;Hooghe & De Vroome, 2015). Furthermore, support for multiculturalism has been found to be associated with the endorsement of minority rights (e.g., Levin et al, 2012;Verkuyten, 2006).…”
Section: Multiculturalismmentioning
confidence: 99%